PROBLEMS OF THE CIVIL SERVANTS SYSTEM IN OSIJEK AT THE TURN OF THE 19TH TO THE 20TH CENTURY (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
The author in the paper present a review and description of legalregulations regarding position of the city officials and civil servants inthe Osijek city administration in the period 1881-1918. Problems of thecivil servants system in the city community of Osijek will be seen inrelation to three groups of questions: the classification of civil servants,the payment system and the progress system. In the introduction theauthor gives legal definition and meaning of the terms official and civilservant. In the central part of the paper the author gives an overview andanalysis normative regulation of the position of city officials andservants, ie status and wages. Legislation regulations that regulated thestatus and position of officials and civil servants, especially the rulebookfrom 1918, started a process that resulted in a growing need for expertise,in addition to experience. The author concludes that the beginnings ofprofessional management can already be noted in the research period aspeople with appropriate qualifications have been employed and thataccomplished organizational solutions meant progress compared toprevious organization.